Assessing subjective memory complaints: a comparison of spontaneous reports and structured questionnaire methods. (3rd July 2014) - Burmester, Bridget; Leathem, Janet; Merrick, Paul
ABSTRACT: Background: Subjective memory complaints (SMCs) are a common occurrence for adults, which increase with age, and cause considerable distress. Traditionally SMCs have been assessed by either questionnaires, which ask whether a person has experienced given examples of SMCs, or open-ended questions which elicit spontaneous reports of SMCs. However, little is known about how these methods of assessment might influence reporting of SMCs. Methods: Four hundred and twenty one adults aged 40 years and above were surveyed about SMCs using spontaneous report and questionnaire methods. Results: As expected, spontaneously reported SMCs were fewer in number and rated more distressing overall than SMCs endorsed on a questionnaire. However, comparison of individual SMCs revealed that distress ratings tended to be higher when assessed in a questionnaire than spontaneously reported, which may be due to the context of a questionnaire causing inflated ratings. Participants also reported SMCs which were not well assessed by the questionnaire, including some which were among the most distressing SMCs overall. Conversely, other SMCs were over-sampled by the questionnaire and did not feature in spontaneous reports. Conclusions: Implications for clinical assessment of SMCs are that open-ended questioning might be preferable to initial use of prescriptive questionnaires, in order to elicit SMCs that are most distressing. While use of questionnaires may reveal endorsement of a wider range of SMCs than are spontaneously reported, they can take focus away from, or even fail to assess, those SMCs which cause most subjective distress (and therefore should be the target of interventions).